2019
DOI: 10.1590/rbz4820180134
|View full text |Cite
|
Sign up to set email alerts
|

Canopy structure and forage nutritive value of elephantgrass subjected to different stocking rate and N fertilization in the “Mata Seca” ecoregion of Pernambuco

Abstract: The objective was to evaluate the effect of three stocking rates (2, 3.9, and 5.8 animal units ha −1) and three fertilization levels (0, 150, and 300 kg N ha −1 yr −1) on herbage mass and nutritive value of elephantgrass (Pennisetum purpureum Schum.) cv. IRI-381. The experiment was conducted from May to August of 2009 and 2010 in Itambé, PE, Brazil, during the rainy season. Treatments were allocated in a split-plot arrangement in a completely randomized block design. The variables measured included leaf mass (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Furthermore, the highest N level increased the root decomposition. Moreover, DOURADO et al (2019) observed an increase of leaf productivity from 10.0 to 18.5 Mg ha -1 DM in an experiment with the same conditions and applied N levels. The authors emphasized the great N extraction capacity from the radicular system of the 'IRI-381' genotype.…”
Section: Nitrogen Fertilization and Irrigationmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, the highest N level increased the root decomposition. Moreover, DOURADO et al (2019) observed an increase of leaf productivity from 10.0 to 18.5 Mg ha -1 DM in an experiment with the same conditions and applied N levels. The authors emphasized the great N extraction capacity from the radicular system of the 'IRI-381' genotype.…”
Section: Nitrogen Fertilization and Irrigationmentioning
confidence: 68%
“…The stocking rate also is an important aspect of grazing management, because the adopted stocking rate above the pasture carrying capacity is one of the most determinant factors of pastureland degradation all over the country (GAlDINo et al, 2013). DOURADO et al (2019) evaluated the leaf blade dry mass of the tall-sized genotype 'IRI-381' in pastures under 2.0, 3.9, and 5.8 AU ha -1 stocking rates and found values of 6,078, 2,543, and 1,670 kg ha -1 , respectively. Moreover, the authors observed a decreasing from 31 to 15% of the leaf blades after pre-grazing, in the function of the stocking rate increase.…”
Section: Grazing Managementmentioning
confidence: 99%
“…For most tropical perennial grass species, such as Pennisetum purpureum Schum. ‘IRI‐381’ (Dourado et al, 2019) and Urochloa brizantha ‘Piatã’ (Zanine et al, 2020) linear increases on pre‐grazing herbage mass, leaf mass and LAI are commonly verified with increasing N fertilisation rates. On the other hand, when grazing strategies are adopted, for a given tropical perennial grass species, considering the ideal range of pre‐ and post‐cutting canopy heights, recent literature has showing that some plant responses may act buffering the increasing herbage mass in response to N fertilisation.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, elephant grass (Pennisetum purpureum Schum.) presents itself as one of the main options for forage production, given its potential to produce forage mass, combined with its nutritional value and acceptability by ruminant animals (Dubeux Jr. and Mello, 2010;Cunha et al, 2011;Dourado et al, 2019;Souza et al, 2021). This forage grass is grown in tropical, subtropical, and even in semiarid zones worldwide (Pereira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%